2018
DOI: 10.22271/ortho.2018.v4.i4a.07
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of closed intramedullary elastic nailing vs plate osteosynthesis in diaphyseal fractures of both bones forearm in adults

Abstract: Background: In the current era, fractures of forearm bones have become more common. The forearm serves an important role in the functioning of the upper extremity. Hence aggressive management through good anatomical reduction and internal fixation of these fractures has become a necessity. Fractures of the radius and ulna occupy a large field of the modern traumatology. Therefore, these fractures are a major subject in modern orthopaedics and traumatology. The purpose of this study was to assess and compare fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
(1 reference statement)
0
0
1
Order By: Relevance
“…This study was quite similar to the current research work as an excellent result according to Anderson scoring system was shown in 13 cases (61.9%), which is quite near to the results shown by the study mentioned above with 50 cases (65.74%). Garampalli et al 23 published a paper with contradictory findings compared to our study. They described the disadvantage of requiring postoperative immobilization until the bridging callus was discovered at the fracture site.…”
Section: Discussioncontrasting
confidence: 99%
“…This study was quite similar to the current research work as an excellent result according to Anderson scoring system was shown in 13 cases (61.9%), which is quite near to the results shown by the study mentioned above with 50 cases (65.74%). Garampalli et al 23 published a paper with contradictory findings compared to our study. They described the disadvantage of requiring postoperative immobilization until the bridging callus was discovered at the fracture site.…”
Section: Discussioncontrasting
confidence: 99%